MARDHATILLAH RELATIONAL STABILITY AS A MEDIATOR BETWEEN KNOWLEDGE DISSEMINATION, SUPPLY CHAIN INTEGRATION, AND ALLIANCE PERFORMANCE IN INDONESIAN SMES - M. Trihudiyatmanto; Bahtiar Efendi; Abiodun Babatunde Onamusi (Journal of Economic, Business and Engineering (JEBE), 2026)
This study aims to analyze the necessity of mardhatillah as a basic concept underpinning supplier-buyer relationships driven by effective knowledge dissemination in buyer-supplier relationships, which is necessary to achieve improved SME alliance performance, considering the mediating role of Mardhatillah Relational Stability and Supply Chain. This study uses a quantitative approach through structural equation modeling (SEM) techniques using partial least squares (SmartPLS 4). Data were collected using a structured questionnaire sent to 140 SMEs that are members of the Indonesian Chamber of Commerce and Industry (Kadin) in the Kedu Regency. Knowledge dissemination (KD) has no influence on alliance performance, but has a significant positive influence on Mardhati Relational Stability and Supply-Chain Integration directly, Mardhati Relational stability mediates the relationship between KD and alliance performance. However, MRS does not mediate the relationship between KD and Supply-Chain. MRS has a significant influence on alliance performance and supply chain integration directly. However, MRS is not mediated by the relationship between Supply-Chain Integration and Alliance Performance. Supply-Chain Integration does not have a direct influence on Alliance Performance and Supply-Chain Integration does not mediate the relationship between KD and Alliance Performance. Implications & Recommendations: For SMEs, the results of this study provide an empirical basis for sharing knowledge aimed at improving the stability of relationships in accordance with the Islamic framework (Mardhatillah) in order to improve Supply-Chain Integration to realize alliance performance in SMEs.